The Effect of Self-Confidence and Mathematics Anxiety on Mathematical Communication Ability of Class IX Students of Madrasah Tsanawiyah - Yuniarti, Yuniarti; Sripatmi, Sripatmi; Azmi, Syahrul; Turmuzi, Muhammad (UNDIKMA, 2023)
This research was conducted at MTsN 1 Mataram in the 2023/2024 school year with the aim of seeing the effect of self-confidence and math anxiety on student’s mathematical communication skills. This type of research is descriptive quantitative research with ex post facto method. The population of this study was class IX MTsN 1 Mataram. In determining the sample, probability sampling technique with cluster random sampling type was used. The sample in this study were students of class IX-4 MTsN 1 Mataram, totaling 32 students. The instruments used in this study were self-confidence questionnaire, math anxiety questionnaire, and mathematical communication ability test. The data analysis technique used was descriptive and inferential statistical analysis. The results of data analysis showed that: (1) The average self-confidence of class IX students of MTsN 1 Mataram in the 2023/2024 school year is in the medium category, where the largest frequency is in the low category with a percentage of 37.50%. The average student math anxiety is in the low category with the largest frequency in the low category at 53.13%. And the average mathematical communication ability of students is in the high category with the largest frequency in the medium category at 40.63%. (2) There is a positive and significant influence between self-confidence on student’s mathematical communication skills by 24.9%. (3) There is a negative and significant influence between math anxiety on student’s mathematical communication skills by 25.6%. (4) There is a significant influence between self-confidence and math anxiety together on student’s mathematical communication skills by 36.4%.